Adaptation to chronic drought modifies soil microbial community responses to phytohormones - Emma J. Sayer (Nature Portfolio, 2021)
Emma Sayer et al. use a 25-year field experiment to investigate how microbial community responses to phytohormones are affected by drought. Phytohormone-induced shifts in microbial functional groups suggest that drought adaptation within soil microbial communities mediates responses to plant stress signalling.